Linkages Between Tourism and Agriculture: The Case of Turkey - Salihoglu, Güliz; Gezici, Ferhan (Springer International Publishing, 2020)
Apart from tourism’s direct economic effects on wages, the development of sectoral relations between tourism and other industries causes firm development and employment generation through the supply demand that arises from the purchase of products and services. Studies conducted on tourism and suppliers often examine relationships with the agricultural sector and highlight these relationships’ positive effects on agricultural product suppliers. The aim of this study is to identify the geographical distribution of the food supply networks of tourism and to explore their secondary economic impacts on the agriculture sector through their supplier relations. This research was conducted in Alanya, one of the most important destinations in Turkey in terms of agricultural production. In this context, the following questions are addressed: Who are the actors in the tourism and food supply process? What are the impacts of tourism on the firms that supply agricultural products? What kind of supplier geography does tourism create with second-tier suppliers? Data was collected through semi-structured interviews with firms in a wholesale market for fresh fruit and vegetables (WM for F&V) in the research area, and non-parametric tests were used to explain their relations with and the impacts of the tourism sector. Furthermore, the supplier network between tourism and agriculture firms was examined to show the geographical economic impact of the sector. The results indicate that hotels are important customers for food supplier firms and that tourism generates strong networks and enhances the supply of agricultural production within and outside the tourism region.